Practical sustainability strategies : how to gain a competitive advantage - Nassos, George P.; Avlonas, Nikos, 1969- (Wiley, 2020)
"Sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their own needs. It is a combination of economic, environmental, and social elements, in that it not only focuses on alleviating pollution and resource conservation, but also addresses poverty, and world trade. During the past few years, there have been many books written on the topic of Sustainability and Corporate Social Responsibility (CSR), however few actually describe the various strategies and practical tools that can be adapted by organizations. There is no question that environmental, social and economic sustainability are critical to the future success of companies, NGO's, government agencies, and other institutions"--